Smart city: problems and solutions (Международный научный журнал «Инженер», 2026)
This article analyzes the concept of a smart city, the importance of the concept of "smart city" for humans, society and nature , and its role in modern urbanization. It also covers the main problems encountered in creating smart cities, including urban planning, infrastructure, technological integration, information security and environmental sustainability. The author offers solutions to these problems based on modern advanced urban planning methods, innovative technologies, digital management systems and ecological approaches. The article also discusses the future of smart cities, their impact on society and development prospects.